2020
DOI: 10.3390/w12123454
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Water and Salt Transport, and Balance Analysis in Sand Dune–Wasteland–Lake Systems of Hetao Oases, Upper Reaches of the Yellow River Basin

Abstract: Desert oases are important parts of maintaining ecohydrology. However, irrigation water diverted from the Yellow River carries a large amount of salt into the desert oases in the Hetao plain. It is of the utmost importance to determine the characteristics of water and salt transport. Research was carried out in the Hetao plain of Inner Mongolia. Three methods, i.e., water-table fluctuation (WTF), soil hydrodynamics, and solute dynamics, were combined to build a water and salt balance model to reveal the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, from a kinetic point of view, the formation of CH 4 , which requires eight electrons, is more difficult than the two-electron reduction of CO 2 to CO. So dynamically it is easier to generate CO. 36,37 We also noticed that no product is detected in the reactor without adding a catalyst, light, CO 2 or water.…”
Section: Resultsmentioning
confidence: 81%
“…However, from a kinetic point of view, the formation of CH 4 , which requires eight electrons, is more difficult than the two-electron reduction of CO 2 to CO. So dynamically it is easier to generate CO. 36,37 We also noticed that no product is detected in the reactor without adding a catalyst, light, CO 2 or water.…”
Section: Resultsmentioning
confidence: 81%
“…Wang et al [42] conducted a 5-year experimental study in the Hetao Irrigation District and found that during irrigation activities, fallow areas act as drainage reservoirs, receiving excess water and salts from surrounding irrigated cultivated lands. Guoshuai Wang et al [43] analyzed water and salt transport in different land types in the Hetao Irrigation District and found that of the groundwater salinity at the wasteland-dune interface, 53% accumulated in the wasteland groundwater and the remaining 47% in the lakes. On the basis of some scholars, this study analyzed the soil water and salt coupling relationship between cultivated and wasteland and concluded that the average coupling coordination degree of soil water and salt of wasteland in the…”
Section: Discussionmentioning
confidence: 99%
“…where n represents the soil desalination rate (%); S i−1 denotes the total soil salt content before irrigation (g/kg); and S i indicates the total soil salt content after irrigation (g/kg). The conversion formula [21] of the EC and the total dissolved solids (TDS) is as follows:…”
Section: Methodsmentioning
confidence: 99%